Gaya Kepemimpinan Paternalistik Kepala Sekolah terhadap Kepuasan Kerja Guru - Sekar Pratiwi; Hana Lestari; Ima Rahmawati (LPPM Institut Nasional Laa Roiba Bogor, 2021)
The purpose of this study was to determine and describe the influence of paternalistic leadership styles on teacher job satisfaction at SDIT AR-Rohmaniyah, Tanah Sareal District, Bogor City. The research method used in this study is a quantitative method using correlational techniques and analyzed using multiple regression techniques. The results of the analysis of the influence of the principal's paternalistic leadership style (X1) on teacher job satisfaction (Y) at SDIT AR Rohmaniyah Kec. Tanah Sareal Bogor City which has been carried out by researchers, from the results of the answers to a questionnaire that has been distributed to 44 respondents using the SPSS version 21 program. Based on the results of a simple linear regression test, it is concluded that there is a positive but insignificant effect between the principal's paternalistic leadership style on satisfaction teacher work.